Dignity and the Death Penalty in the United States Supreme Court - Malkani, Bharat (2017)
The concept of dignity is central to moral and legal issues about the death penalty. The United States Supreme Court has justified the use of dignity to retain the use of the death penalty. However, this article argues that dignity should not be used as a means to uphold the use of capital punishment. Instead, the concept of dignity involves the relationship between the human dignity of the people involved in the crime, the dignity of the wider community in whose name the death penalty is being imposed, and the dignity of the legal institution that administers capital punishment. As of now, the Court has not properly addressed the relationship on these three dignities. If it did so, the Court would have to hold that the death penalty and respect for dignity are inconsistent from each other. This Article addresses the following: (1) how the internationally community has found that the death penalty runs contrary to the respect for human dignity; (2) how the U.S. Supreme Court incorporates dignity into its death penalty jurisprudence; (3) and how philosophical literature regarding dignity helps us understand the U.S. Supreme Court's judicial approaches to human dignity, communitarian dignity, and institutional dignity